Peran Pemerintah Sebagai Pengambil Keputusan dalam Meningkatkan Partisipasi Masyarakat di Kelurahan Bobo Kecamatan Tidore Utara Kota Tidore Kepulauan - Abdul Kadir Ali (Jurnal Ilmiah Wahana Pendidikan, 2022)
The success of village development is an indicator of community welfare in the village. Meanwhile, development in a village is said to be successful, inseparable from the intervention of all existing elements. The community is seen as an important element in the process of implementing urban development, so community participation is important in its success. The role of the community can be seen in real terms, starting from the involvement of planning (Musrembang) to active participation in its implementation. The main reason for community involvement is none other than the planning carried out must represent the interests and needs of the community, so as to improve the welfare of the community.